The association of ARRB1 polymorphisms with response to antidepressant treatment in depressed patients - Chappell, Kenneth; Ait Tayeb, Abd El Kader; Colle, Romain; Bouligand, Jérôme; El-Asmar, Khalil; Gressier, Florence; Trabado, Séverine; David, Denis Joseph; Feve, Bruno; Becquemont, Laurent; Corruble, Emmanuelle; Verstuyft, Céline (Frontiers in Pharmacology, 2022)
Introduction: β-arrestin 1, a protein encoded by ARRB1 involved in receptor signaling, is a potential biomarker for the response to antidepressant drug (ATD) treatment in depression. We examined ARRB1 genetic variants for their association with response following ATD treatment in METADAP, a cohort of 6-month ATD-treated depressed patients. Methods: Patients (n=388) were assessed at baseline (M0) and after 1 (M1), 3 (M3), and 6 months (M6) of treatment for Hamilton Depression Rating Scale (HDRS) changes, response, and remission. Whole-gene ARRB1 variants identified from high-throughput sequencing were separated by a minor allele frequency (MAF)≥5%. Frequent variants (i.e., MAF≥5%) annotated by RegulomeDB as likely affecting transcription factor binding were analyzed using mixed-effects models. Rare variants (i.e., MAF<5%) were analyzed using a variant set analysis. Results: The variant set analysis of rare variants was significant in explaining HDRS score changes (T=878.9; P=0.0033) and remission (T=-1974.1; P=0.034). Rare variant counts were significant in explaining response (P=0.016), remission (P=0.022), and HDRS scores at M1 (P=0.0021) and M3 (P=<0.001). rs553664 and rs536852 were significantly associated with the HDRS score (rs553664: P=0.0055 | rs536852: P=0.046) and remission (rs553664: P=0.026 | rs536852: P=0.012) through their interactions with time. At M6, significantly higher HDRS scores were observed in rs553664 AA homozygotes (13.98±1.06) compared to AG heterozygotes (10.59±0.86; P=0.014) and in rs536852 GG homozygotes (14.88±1.10) compared to AG heterozygotes (11.26±0.95; P=0.0061). Significantly lower remitter rates were observed in rs536852 GG homozygotes (8%, n=56) compared to AG heterozygotes (42%, n=105) at M6 (P=0.0018). Conclusion: Our results suggest ARRB1 variants may influence the response to ATD treatment in depressed patients. Further analysis of functional ARRB1 variants and rare variant burden in other populations would help corroborate our exploratory analysis. β-arrestin 1 and genetic variants of ARRB1 may be useful clinical biomarkers for clinical improvement following ATD treatment in depressed individuals.